1999
DOI: 10.1159/000028824
|View full text |Cite
|
Sign up to set email alerts
|

Cushing’s Disease in a 7-Month-Old Girl due to a Tumor Producing Adrenocorticotropic Hormone and Thyreotropin-Secreting Hormone

Abstract: We present the case of a 7-month-old baby with Cushing's disease due to an adrenocorticotropic hormone (ACTH)-secreting pituitary adenoma combined with cells producing thyreotropin-secreting hormone (TSH). In MRI scans, a contrast-enhancing lesion was seen inside the pituitary fossa, and it extended into the suprasellar region. On the assumption of a pituitary adenoma, surgery was performed. Corresponding with biochemical findings, histopathological evaluation revealed an ACTH- and TSH-producing tumor. Genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In addition, based on the description in the reports, it was considered that three further cases probably represented PitB [13, 14, 17]. The clinical presentations and tumor histopathology of each PitB were strikingly similar, but the main predisposing genetic factors were not known.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the description in the reports, it was considered that three further cases probably represented PitB [13, 14, 17]. The clinical presentations and tumor histopathology of each PitB were strikingly similar, but the main predisposing genetic factors were not known.…”
Section: Introductionmentioning
confidence: 99%
“…This observational study comprised a multi-institutional cohort of 17 patients with pituitary blastoma: updating 14 previously described cases (1)(2)(3)(4)(20)(21)(22)(23)(24)(25)(26)(27)(28) and fully characterizing three additional cases (16)(17)(18). Cases were identified by ongoing literature review, inquiries to leading pituitary experts and case referrals.…”
Section: Design and Study Cohortmentioning
confidence: 99%
“…Since the reports by Sahakitrungruang et al (1 case) and de Kock et al (13 cases), three additional cases of pituitary blastoma have been thoroughly investigated (1)(2)(3)(4)(16)(17)(18)(20)(21)(22)(23)(24)(25)(26)(27)(28). In 2010, Salunke et al reported a 2-month-old female with Cushingoid stigmata since birth, ophthalmoplegia, hemiparesis, and a pituitary tumor diagnosed as a "congenital immature teratoma" (Case 17; Table 1) (30,31); the pathology on review was consistent with pituitary blastoma (16).…”
Section: Recently Investigated Cases Of Pituitary Blastomamentioning
confidence: 99%
“…TSHomas usually secrete alpha-subunit of the glycoprotein hormones (α-SU) and less frequently growth hormone (GH) and/or prolactin (PRL), ACTH, and FSH/LH [5]. Until now, only nineteen paediatric cases have been proven to have pituitary TSHoma in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Almost all of them had macroadenoma and presented with symptoms of hyperthyroidism and/or goitre [6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22]24].…”
mentioning
confidence: 99%